The role of sea ice in the carbon cycle of polar oceans - Moreau, Sébastien; Vancoppenolle, Martin; Crabeck, Odile; Delille, B.; Brown, Karina; Campbell, Karley; Chierici, Melissa M.C.; Else, Brent; Fransson, Agneta A.F.; Fripiat, François; Geilfus, Nicolas Xavier; Jones, Elisabeth; et al. (2023)
info:eu-repo/semantics/nonPublished